Profil Kemampuan Pemecahan Masalah Siswa SMA Pada Materi Ekosistem: (Profile of Problem Solving Capabilities of High School Students in Ecosystem Materials) - Ira Rahma; Sistiana Windyariani; Suhendar Suhendar (BIODIK, 2020)
This study aims to describe the profile of problem-solving abilities on each indicator according to Pannen (in Rusmono, 2012). The research used is descriptive method. The sample used is 35 students who have studied the ecosystem material. The sample selection technique used in this study was purposive sampling, which is a sample collection technique with certain considerations, subject taking is not based on strata, random or regional but is based on the existence of certain objectives. This research was conducted in FEBRUARY 4th week of 2020. The instrument used was a test question for the description of problem-solving abilities, amounting to 12 questions. The results showed that the problem-solving ability profile had a percentage of 59% in the sufficient category. The results include three categories, namely; 1) the good category consists of indicators of identifying problems by 75% and collecting 66% of data, 2) sufficient categories consisting of indicators of solving problems based on data by 55%, choosing ways to solve problems by 61%, and planning to implement problems by 57% . 3) the less category consists of indicators of analyzing data / problems by 40%. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan profil kemampuan pemecahan masalah pada setiap indikator menurut Pannen (dalam rusmono, 2012). Penelitian yang digunakan ialah metode deskriptif. Sampel yang digunakan sebanyak 35 siswa yang telah mempelajari materi ekosistem. Teknik pemilihan sampel yang di gunakan dalam penelitian ini adalah menggunakan purposive sampling, yaitu teknik pengumpulan sampel dengan pertimbangan tertentu, pengambilan subjek bukan di dasarkan atas strata, random atau daerah tetapi di dasarkan atas adanya tujuan tertentu. Penelitian ini dilaksanakan pada bulan FEBRUARI minggu ke-4 tahun 2020. Instrumen yang digunakan berupa soal tes uraian kemampuan pemecahan masalah yang berjumlah 12 soal. Hasil penelitian menunjukkan profil kemampuan pemecahan masalah memiliki persentase sebesar 59% dengan kategori cukup. Adapun hasil tersebut mencakup tiga ketegori ialah; 1) Kategori baik terdiri dari indikator mengidentifikasi masalah sebesar 75% dan mengumpulkan data 66%, 2) Kategori cukup terdiri dari indikator memecahkan masalah berdasarkan data sebesar 55%, memilih cara untuk memecahkan masalah masalah sebesar 61%, dan merencanakan penerapan masalah sebesar 57%. 3) Kategori kurang terdiri dari indikator menganalisis data/masalah sebesar 40%.